SIMULATION AND ANALYSIS OF HARMONIC DETECTION AND MITIGATION SYSTEM USING ACTIVE FILTER - MIZA, BELIA (Universiti Malaysia Sarawak, (UNIMAS), 2019)
The most frequent problems in power system is known as harmonics. This harmonic distortion causes by non-linear loads such as computers, printers, non-incandescent lighting, variable speed drives and programmable logic controllers (PLCs). In this era of technology, many electronics devices used in the residential area and industrial area contribute to the power quality issue, which is harmonics. Therefore, analysis of harmonic detection using Fast Fourier Transform (FFT) is one of the initiatives for power quality monitoring. The main objective for this study is to analyse the harmonics components in AC power system using Fast Fourier Transforms (FFT) algorithm. Other than that, the objective is also to design and develop the harmonic detection system for power quality of AC power system. In addition, this objective of this paper is to study of method of harmonics mitigation using the designed active filter to obtain better quality of signal in power system. This analysis is mainly to analyse the quality of power signal for power data collection, processing and analysis. A method to mitigate the harmonic distortion in power system are studied so that any low-quality power system issue can be improved from time to time.